Traumatic rupture of the posterior deltoid tendon during weight lifting: A case report and review of literature. Issue 8 (9th April 2021) - Sanderson, Brent; Bogard, Michael; Jazayeri, Reza
Abstract: Deltoid tendon humeral sided avulsion leads to discomfort and functional limitation in the young active population. This report illustrates a case for surgical treatment with a simple suspensory device that allows for early return to activity. Abstract : Deltoid tendon humeral sided avulsion leads to discomfort and functional limitation in the young active population. This report illustrates a case for surgical treatment with a simple suspensory device that allows for early return to activity.